2017
DOI: 10.1016/j.scitotenv.2016.10.151
|View full text |Cite
|
Sign up to set email alerts
|

Contextual and interdependent causes of climate change adaptation barriers: Insights from water management institutions in Himachal Pradesh, India

Abstract: Research on adaptation barriers is increasing as the need for climate change adaptation becomes evident. However, empirical studies regarding the emergence, causes and sustenance of adaptation barriers remain limited. This research identifies key contextual causes of adaptation barriers in water institutions in the mountainous Himalayan state of Himachal Pradesh in northern India. Semi-structured interviews were carried out with representatives from twenty-six key governmental, non-governmental, academic and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 49 publications
2
17
0
Order By: Relevance
“…Notably, in the financial year 2016/2017, the Natural Resource and Production and Marketing departments that are directly mandated to handle natural resource management and agriculture issues, were allocated 0.02% and 0.37% of the Total budget [44]. This is in tandem with [16] who reported that inadequate funding and budgetary allocation to the concerned departments was a big challenge to climate variability and change adaptation in Uganda which clearly agrees with the study findings.…”
Section: Inadequate Fundingsupporting
confidence: 89%
“…Notably, in the financial year 2016/2017, the Natural Resource and Production and Marketing departments that are directly mandated to handle natural resource management and agriculture issues, were allocated 0.02% and 0.37% of the Total budget [44]. This is in tandem with [16] who reported that inadequate funding and budgetary allocation to the concerned departments was a big challenge to climate variability and change adaptation in Uganda which clearly agrees with the study findings.…”
Section: Inadequate Fundingsupporting
confidence: 89%
“…While some nationally or globally comprehensive studies on barriers exist (Bierbaum et al, 2013;Biesbroek et al, 2013) most research has been context specific (e.g., Azhoni et al, 2017;Carmin et al, 2012;Measham et al, 2011;Raymond & Robinson, 2013). This study sought to follow this trend of location-specific studies while filling a gap focusing on a unresearched geography.…”
Section: Academic Workmentioning
confidence: 99%
“…With such localized planning, it is important to understand where gaps exist in community planning research. Additionally, barriers preventing adaptation planning and implementation have been noted by Beisbroek et al (2013) as 'potentially endless' (Azhoni et al, 2017;Cuevas, 2016;Eisenack et al, 2014) and highly contextual and interdependent (Eisenack et al, 2014). With such localized planning and context-dependent barriers an understanding of climate change adaptation planning in the understudied rural, non-agricultural-based context, is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Inaccessibility to information and data was found to result from barriers including negative work culture and attitudes, resource limitations, and weak intra‐institutional networks. Inaccessibility to information and data was in turn found to propagate governance challenges and result in low implementation of adaptation options (Azhoni et al, ). This study draws attention to the context in which data is collected, stored, and made publicly accessible (or not) and highlights a wider set of challenges for attention before BDAs can realistically provide input to coastal flood risk assessment.…”
Section: Bdas For Coastal Flood Risk Assessmentmentioning
confidence: 99%